Aspek Hukum Pengangkatan Wali Anak di Bawah Umur Dalam Praktek Pengadilan (Studi Penetapan Nomor: 220/Pdt.P/2024/PN.Tjk) - Sari, Silviana; Baharrudin, Baharrudin; Aprinisa, Aprinisa (Jurnal Akuntansi Hukum dan Edukasi, 2025)
Guardianship of minors in law is a mechanism that aims to protect the rights and interests of children whose parents are unable to carry out their roles, either because they have died, lost custody rights, or are legally incompetent. Guardianship is given to a guardian appointed by the court, either from the child's immediate family or another party who is deemed capable of meeting the child's physical and psychological needs. Guardians are responsible for managing the child's assets and ensuring their welfare, while remaining supervised by the court or related agencies to prevent abuse of authority. This research examines the legal aspects of appointing guardians of minors based on Determination Number: 220/Pdt.P/2024/PN.Tjk. The research methodology is normative juridical, employing an analytical approach to relevant laws and documents. Data collection was conducted through library research and field research. The data analysis method used is qualitative juridical analysis. The research results show that in Determination Number : 220/Pdt.P/2024/Pn.Tjk, the legal procedure for appointing a child's guardian includes two main stages, namely the registration and trial stages. At the registration stage, the applicant submits application documents for verification, while at the trial stage, evidence and witnesses are presented to support the application. If the application meets the requirements, the court grants a guardianship order. The legal consequence of this determination is the transfer of guardianship responsibility to a legally authorized guardian, who has special authority in making decisions regarding the child's interests, including education until adulthood. This stipulation also regulates supervision from the Social Service to ensure the fulfillment of children's rights in accordance with Law Number 23 of 2002 concerning Child Protection.